PENERAPAN PEMBINAAN EKSTRAKURIKULER DALAM KEGIATAN PEMBELAJARAN FULL DAY SCHOOL - Selvia, Belva; Lian, Bukman; Sari, Artanti Puspita (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2020)
This research aimed at determining how the application of extracurricular coaching in full day school study activities at SMP Negeri 1 Indralaya Utara in 2019. The writer used a qualitative approach. Data ware obtained from the principal, teachers, parents and students. Data analysis was conducted based on the results of document reviews, interviews and observations. The results of the research showed that extracurricular coaching in the full day school study activities was done in several ways. For examples: a) during time of self development activities on Friday, b) through routine meetings on Wednesday during recess, c) conducted according to a predetermined schedule, and d) carried out intensively in preparation for competitions. The inhibiting factors in the implementation of extracurricular coaching were lack of time effectiveness, lack of student interes in joining extracurricular activities, and parents who restricted their children from attending extracurricular activities due to the relatively remote distance between school and their homes.